1955
DOI: 10.1136/oem.12.2.169
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Dermatitis Caused by Ethylene Oxide

Abstract: Ethylene oxide exists as a colourless gas at ordinary temperatures. but at 10.70 C. it condenses to form a water-white liquid. It is miscible with water in all proportions and forms hydrates. It combines with compounds having a labile hydrogen atom such as water, alcohols, ammonia, and organic acids, although at ordinary temperatures some of these reactions are very slow. It will also abstract the elements of hydrochloric acid from aqueous solutions of chlorides forming ethylene chlorhydrin thereby yielding al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

1968
1968
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 4 publications
0
7
0
1
Order By: Relevance
“…Tbe source of hand irritation from gloves in hospital environtTients has not been very widely investigated. Only occasionally bacterial endotoxin in latex gloves sterilized with gamma irradiation [20] and ethylene t>xide gas used in sterilization of disposable gloves [21] have been associated with dermatitis. Our study showed that cornstarch powder and perhaps latex proteins, as well as warmth and moistness established under the gloves, are very important causes of irritant CD.…”
Section: Discussionmentioning
confidence: 99%
“…Tbe source of hand irritation from gloves in hospital environtTients has not been very widely investigated. Only occasionally bacterial endotoxin in latex gloves sterilized with gamma irradiation [20] and ethylene t>xide gas used in sterilization of disposable gloves [21] have been associated with dermatitis. Our study showed that cornstarch powder and perhaps latex proteins, as well as warmth and moistness established under the gloves, are very important causes of irritant CD.…”
Section: Discussionmentioning
confidence: 99%
“…Andererseits konnte in Versuchen zur Bestimmung der Hauttoxizität Ethylenoxid-sterilisierter Materialien mit unterschiedlichen Ethylenoxid-Rückstandsmengen bei einer der Versuchspersonen eine Sensibilisierung nachgewiesen werden [24]. Im medizinischen Bereich kam es infolge der Freisetzung von Ethylenoxid-Rückständen insbesondere aus entsprechend sterilisiertem Anästhesiezubehör, wie Narkosemasken [25][26][27], Gummihandschuhen [28], Endotrachealtuben [27,29] und Tracheostomietuben, [30,31] [36].…”
Section: Erfahrungen Beim Menschenunclassified
“…In the medical sector, ethylene oxide residues released from sterilized anaesthetic equipment such as narcosis masks [25][26][27], rubber gloves [28], endotracheal tubes [27,29] and tracheostomy tubes [30,31] led to sometimes severe local irritation of skin and mucous membranes and to stenosis. When materials sterilized with ethylene oxide were used for an extracorporeal bypass, the high residue levels caused haemolysis, increased levels of free haemoglobin and renal complications in the patients [32].…”
Section: Effects In Manmentioning
confidence: 99%